GAMBARAN PENGETAHUAN TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA SISWA KELAS EMPAT DAN LIMA DI SDN 23/IX PONDOK MEJA - Silfia, Aida; Sri Gumilar, Mira; Salsabila, Nadiya (NHM PRESS, 2024)
Knowledge of dental and oral health in children is crucial for improving their behavior in maintaining oral hygiene. Behaviors developed from childhood will have a positive impact in adulthood. This research aims to describe the knowledge of how to maintain dental and oral health among 4th and 5th-grade students at SDN 23/IX Pondok Meja. The research method used is a descriptive survey method. The study population consists of 46 students, with 21 students in 4th grade and 25 students in 5th grade. This study employed total sampling, meaning the entire population was sampled. The measuring instrument used was a questionnaire. The results of this study showed that knowledge of dental and oral health maintenance among 4th and 5th-grade students at SDN 23/IX Pondok Meja in 2024 included the following: in brushing teeth, 28% had high knowledge, 50% had medium knowledge, and 22% had low knowledge. Knowledge about food impacting oral health was 63% for high criteria, 33% for medium criteria, and 4% for low criteria. Knowledge about using health services to maintain oral health was 28% for high criteria, 52% for medium criteria, and 20% for low criteria. The students' knowledge about dental and oral health is best in the area of foods that promote dental health, whereas their knowledge is less comprehensive regarding regular dental check-ups at health facilities.